PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PRODUKSI ASI PADA IBU NIFAS - Octaviani Iqmy, Ledy; Siti Lathifah, Neneng (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Abstract: Increased breast milk production is affected by the presence of polyphenols and steroids in the heart of a banana. Steroids in the heart of bananas that affect the prolactin reflex to stimulate alveoli that work actively in the formation of breast milk. Polyphenols affect the increase in the hormone oxytocin, oxytocin is a hormone that acts to encourage the secretion of milk. Based on the results of the survey conducted by researchers at BPM Wirahayu Panjang in August 2018, of the 10 postpartum mothers, 6 (60%) of postpartum mothers whose less breast production and 4 (40%) postpartum mothers with smooth breastfeeding. While from the total postpartum mothers in August 2018, postpartum mothers who did not breastfeed were 14 people (33.3%) and only 28 people (66.6%) were breastfeeding. The purpose of this study was to determine the Effect of Banana Heart Consumption on Breast Milk Production in Postpartum Mothers in the Wirahayu Panjang BPM Working Area in Bandar Lampung in 2019. This type of research uses quantitative research with a pre-experiment approach with the design of Two Group Pretest-Postest. The population in this study were all postpartum mothers who delivered at BPM Wirahayu Panjang with an average birth rate in April-June 2019 of 120 people. The sample in this study were all postpartum mothers at the time of the study which met the sample criteria. The number of samples in this study were 60 people, with details of 30 case groups and 30 control groups. The statistical test used is the Independent T-Test. Statistical test results obtained the P-Value 0.026 <Î± (0.05), which means that there is an influence of consumption of banana heart on breast milk production in BPM Wirahayu Panjang 2019. The results of this study need further research using multivariate analysis. For practice land or BPM can be used as one of the menu references that can be included in the puerperal food menu.